A Taqriz for a Nineteenth Century Indonesian Manuscript - Nico J.G. Kaptein (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
In medieval Arabic literature a taqr³§ is a written endorsement of a certain text, which a prestigious scholar provides at the request of another scholar to support the latter’s new writing. In this sense it can be compared to the contemporary “blurb”, to advertise a new book. The taqr³§ is important because it connects and offers insights into active networks of like-minded scholars. Unfortunately this topic is still insufficiently studied and the present paper aims to make a contribution to this subject. The research examines an original taqr³§ from the nineteenth century which a scholar in Batavia obtained from his former teacher in Mecca. The paper shows that the taqr³§ is also in existence in more modern times and even beyond the Arab world.